SISTEM KENDALI PERGERAKAN MOBILISASI MENGGUNAKAN GESTUR TANGAN PADA AUTONOMOUS ROBOT GUN (ARO-GUN) - Arifanto, Bima; Muhtar, Ali; Prasetyawan, Purwono (Injection: Indonesian Journal of Vocational Mechanical Engineering, 2023)
Existing mobile weapon technologies can endanger its user because of the need to use direct control, while also having a heavy mass that can slow down movement speed. In this study, a product called ARO-GUN is developed to have multiple functions, which are accurately shot targets, remotely controlled, utilizes hand gestures, also having a light mass. Testing is done by looking at the accuracy of the angle, speed, and response time so that the percentage of error can be seen based on predetermined parameters. The test results shown that there are errors in each tests, namely 1.89% for the accuracy of the hand gesture sensor, 18.98% for the transceiver response time, 10.75% for the rotational speed, and 17.92% for the response to the movement of the weapon.Based on study results, it can be concluded that ARO-GUN product can be operated as a mobile weapon by utilizing hand gestures for controlling its movement direction with maximum distance of 18 meter. Beside that, ARO-GUN has a speed of 300 rpm and a mass of 4.30 Kg, which is lighter than most mobile weapon technologies.